Implementation and challenges of English language education reform in Malaysian primary schools - Hazita Azman, (Penerbit Universiti Kebangsaan Malaysia, 2016)
This article elucidates the implementation of English as a second language (ESL) learning and teaching programmes at the primary school level, spanning three decades of English language education (ELE) in Malaysia, its reform initiatives as well as the arising realities. The realities highlighted underscore the paradoxical challenges experienced with each ELE reform that are introduced, arising from the multilingual and plural socio-political circumstances of the country. In particular, among recent reforms that are examined, is the consequence that the new Primary School Standards-Based Curriculum for English language education (SBELC), which was introduced in 2011, has on the literacy performance of year three pupils when they sit for the LINUS LBI (literacy and Numeracy Screening for English Literacy) test, and the extent to which the English teachers and these young learners are ready to embrace the new curriculum. Concurrently, a review of the Malaysia Education Blueprint (2013-2025) as well as the Malaysia English Language Roadmap (2015-2025), is undertaken and their implications for yet another major language in education reform juxtaposed against existing problems related to teacher’s language proficiency, inadequate trained and skilled teachers, mismatch between curriculum and practices, limited language exposure, and most significantly, the foreboding view of the English language as a threat towards maintaining multilingual plurality, are duly extrapolated. By way of conclusion, this article draws upon selected innovative practices to illustrate the creative pathways that have emerged from these multifarious circumstances and have ironically shown potential in strengthening the young learners’ English language proficiency, notwithstanding identified impeding factors.